Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

Simplify <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>5</mn><mo>+</mo><mi>y</mi><mo>)</mo></mrow><mo>⋅</mo><mn>5</mn></mstyle></math> .

Start simplifying.

Simplify by adding zeros.

Apply the distributive property.

Simplify the expression.

Multiply <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> to the left of <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mrow><mo>(</mo><mi>y</mi><mo>-</mo><mn>3</mn><mo>)</mo></mrow><mo>⋅</mo><mn>7</mn></mstyle></math> .

Apply the distributive property.

Simplify the expression.

Move <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> to the left of <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Move all terms containing <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to the left side of the equation.

Subtract <math><mstyle displaystyle="true"><mn>7</mn><mi>y</mi></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>7</mn><mi>y</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>5</mn><mi>y</mi></mstyle></math> .

Move all terms not containing <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to the right side of the equation.

Subtract <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mn>21</mn></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mo>-</mo><mn>46</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mo>-</mo><mn>46</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Divide <math><mstyle displaystyle="true"><mo>-</mo><mn>46</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Do you know how to Solve for y (5+y)/(y-3)=14/10? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.